1997
DOI: 10.1210/jcem.82.9.4238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemotherapy-Induced Testicular Damage on Inhibin, Gonadotropin, and Testosterone Secretion: A Prospective Longitudinal Study

Abstract: To investigate the role of inhibin in the control of follicle-stimulating hormone (FSH) secretion, we have measured levels of immunoreactive inhibin (ir-inhibin), inhibin B, Pro-alpha C containing inhibins, FSH, luteinizing hormone (LH), and testosterone in twelve men with hematological malignancies before, during, and after chemotherapy. Inhibin B levels fell significantly by 1 month from a mean +/- SE baseline level of 273.2 +/- 32.8 pg/mL, reaching a nadir of 52.6 +/- 15.3 pg/mL at 4 months (P < 0.0001). FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
7

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 41 publications
1
32
0
7
Order By: Relevance
“…Inhibin B levels are reduced in patients with spermatogenic failure and show a reciprocal relationship with FSH during chemotherapy-induced spermatogenic damage. 7 In our study we observed a significant correlation of inhibin B levels with sperm counts. However, while all five patients with very low inhibin B levels were azoospermic, inhibin B levels did not reliably distinguish the non-azoospermic patients from the other four azoospermic patients.…”
Section: Discussionsupporting
confidence: 59%
“…Inhibin B levels are reduced in patients with spermatogenic failure and show a reciprocal relationship with FSH during chemotherapy-induced spermatogenic damage. 7 In our study we observed a significant correlation of inhibin B levels with sperm counts. However, while all five patients with very low inhibin B levels were azoospermic, inhibin B levels did not reliably distinguish the non-azoospermic patients from the other four azoospermic patients.…”
Section: Discussionsupporting
confidence: 59%
“…19 We found a negative correlation between inhibin B and FSH concentrations. Wallace et al 20 found that inhibin B fell 1 month after chemotherapy for hematological malignancies, and that FSH increased within the first month. Both reached plateau values at 4 months, did not change thereafter until 12 months, and were significantly and negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these alterations were accurately surmised as being detrimental to fertility, but the limitations of these studies prevented meaningful application in clinical practice (Hensley and Reichman, 1998). Prospective studies are limited and have been performed in women and men with haematological malignancy (Chatterjee et al, 1994;Wallace et al, 1997).…”
Section: P<001mentioning
confidence: 99%